2014
DOI: 10.4491/ksee.2014.36.7.498
|View full text |Cite
|
Sign up to set email alerts
|

The Concentrations of Ambient VOCs at Industrial Complex Area in Daegu City

Abstract: This study was carried out to characterize the ambient VOCs concentrations of industrial complex in Daegu city. VOCs concentrations of industrial complex area appeared to be higher than those in the non-industrial complex area as following order toluene > ethylbenzene > m,p-xylenes > o-xylene but benzene and chloroform were similar to each other sites. There was seasonal variation of VOCs concentrations in the industrial complex area, higher in summer and lower in winter. In particular the industrial complex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Among air sampling data, MEK was detected relatively frequently from both industrial complexes and schools, and this could indirectly show that schools are affected by pollutants emitted from industrial area. Also, it is reported that the concentration of heavy metals-such as nickel and cadmium [33]-and VOCs-such as toluene, ethylbenzene, and xylene [34]-is higher in the vicinity of the "Daegu Third Industrial Complex " than in other regions of Daegu.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…Among air sampling data, MEK was detected relatively frequently from both industrial complexes and schools, and this could indirectly show that schools are affected by pollutants emitted from industrial area. Also, it is reported that the concentration of heavy metals-such as nickel and cadmium [33]-and VOCs-such as toluene, ethylbenzene, and xylene [34]-is higher in the vicinity of the "Daegu Third Industrial Complex " than in other regions of Daegu.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%